Interest Rate Policies, Stabilization, and Bank Supervision in Developing Countries : Strategies for Financial Reforms. (IMF Working Papers; Working Paper ;, 1990)
This paper identifies macroeconomic stability, effective bank supervision, and an appropriate sequencing of stabilization, banking regulations, and interest rate policies as common characteristics of the relatively successful experiments in financial sector liberalization. Recent theoretical developments help to explain why interest rates in free markets for bank credit may fall short of market-clearing levels, or may rise to risky levels with adverse consequences for financial institutions and the economy at large. To prevent such outcomes, macro-economic stabilization and improved bank supervision should generally precede complete removal of control on bank interest rates.